From the History of Pedagogical Problems of the Development of the People's Practical Decorative Art - Ibragimov X.X. (Academia One Publishing, 2023)
In the long history of the peoples of the East, even in the early stages of the emergence of mankind, for example, in the system of the primitive community, in the system of the slave society, attention was paid to the education of young children and the future generation. In the primitive community system, at first they were taught to make pitchforks and sharp spears from wood and to hunt with them, then they were taught to set handles for various stones, brass, bones, etc., to work with them, to hunt, and to make various tools. With the slavery system, the making of wooden tools, handles, and devices was improved, they were made so that they could fulfill their purpose, giving a unique quality, polish, and perform their tasks, and these things were taught to children and students
Keywords: education; buckets; bowls; plates